An integrated neuro-genetic approach incorporating the Taguchi method for product design. Issue 1 (January 2015) - Lin, Ming-Chyuan; Lin, Yi-Hsien; Lin, Chun-Chun; Chen, Ming-Shi; Hung, Yu-Ching
Highlights An integrated engineering design procedure is proposed for product development. A neuro-genetic approach is applied to search for more precise design solution. The concept of fractal theory is applied in the product form generation.